6 Effects of Long-term Testosterone Therapy on Erectile Function in Obese Men with Functional Hypogonadism Receiving Long-term Testosterone Therapy- results From a Registry Study. Issue 1 (1st April 2022) - Haider, A; Haider, KS; Doros, G; Traish, A; Saad, F
ABSTRACT: Introduction: Erectile dysfunction (ED) is common in men with obesity and hypogonadism. We have previously shown long-term testosterone therapy (TTh) to result in improved erectile function and reductions in waist circumference (WC) and weight in obese men with hypogonadism with different etiologies. The FDA advises against treating hypogonadism in men with non-organic, age-related ("functional") hypogonadism. Objective: to investigate effects on erectile function, waist circumference and weight in with functional hypogonadism receiving long-term TTh up to 12 years, compared with an untreated control group. Methods: In a registry study in men with hypogonadism (defined by total testosterone ≤350 ng/mL and at least moderate symptoms assessed by the Aging Males' Symptoms scale) in a single urology office, men with primary hypogonadism were excluded from the analysis. 476 men had functional hypogonadism and were obese (BMI ≥30 kg/m²). 281 men received testosterone undecanoate (TU) injections 1000 mg/12 weeks following an initial 6-week interval (T-group), 195 opted against TTh and served as controls (CTRL). IIEF-EF (5+1 questions, maximum score: 30), WC, and weight were assessed at each visit. Changes over time between groups were compared by a mixed effects model for repeated measures with a random effect for intercept and fixed effects for time, group and their interaction and adjusted for age, weight, waist circumference, blood pressure, fasting glucose, lipids and quality of life to account for baseline differences between groups. Results: Mean (median) follow-up: T-group 9.4±3.0 (12), CTRL 8.9±3.0 (12) years, total observation time: T-group 2630, CTRL 1737 years. Baseline age was 59.9±5.5 (T-group) and 62.9±5.0 years (CTRL) (p<0.0001). At baseline, PDE5-Inhibitors were used by 23.1% (T-group) and 26.2% (CTRL) (p=0.4501). ED was reported at first visit by 62.3% in the T-group and by 40.5% in CTRL. In patients not reporting ED, ED was diagnosed by use of the IIEF-EF in 30.2% and 58.5%, respectively. 7.5% in the T-group and 1% in CTRL had no ED (p<0.0001 for all). Erectile function: In the T-group, IIEF-EF increased by 11.1±0.3 (least squares means ± standard errors) in year 12. In CTRL, IIEF-EF decreased by 14.4±0.4. The estimated adjusted difference between groups was 25.5 (95% CI: 24.5;26.5) (p<0.0001 for all). WC: In the T-group, WC decreased by 13.7±0.3 cm in year 12. In CTRL, WC increased by 8.1±0.4. The estimated adjusted difference between groups was -21.8 (95% CI: -22.9;-20.7) (p<0.0001 for all). Weight: In the T-group, weight decreased by 23.7±0.4 kg in year 12. In CTRL, weight increased by 7.3±0.5. The estimated adjusted difference between groups was -31.0 (95% CI: -32.5;-29.6) (p<0.0001 for all). Adherence to TTh was 100 per cent as all injections were administered in the office and documented. Conclusions: Long-term testosterone therapy in obese men with functional hypogonadism improved erectile function and resulted in reductions in waist circumference and weight. In the untreated control group, erectile function and anthropometric parameters deteriorated. Disclosure: Yes, this is sponsored by industry/sponsor: Bayer Clarification: Industry funding only - investigator initiated and executed study Any of the authors act as a consultant, employee or shareholder of an industry for: Bayer